V-shaped bending support’ membantu dalam eksperimen ‘3-point bending test’ untuk tikus bersaiz kecil (V-shaped bending support helps in 3-point bending test experiment for small mice bone) / Noor Shafini Mohamad and Mohd Hafizi Mahmud - Mohamad, Noor Shafini; Mahmud, Mohd Hafizi (Universiti Teknologi MARA, 2020)
Three-point bending test is one of the main methods used in long bones to characterise bone material and determine the biomechanical properties. We have examined the mechanical competencies of the mouse bones at four-week-old by using a three-point bending jig so that the potential genotype-related deficiencies in mechanical properties of bones explored. The available bending jig was not suitable for small animal model and may cause slippage when applying the load. The tibial gross length measurements of the four-week-old mouse measured using the proximal anatomical point of the centre of the condyles to the distal anatomical significance of the medial malleolus (~16 mm). The mid tibia diameter measurement is taken at the middle tibia (~1 mm) and metaphyseal diameter (~3 mm). The bending jig was custom-made, where both ends support were cut in a v-shape to provide stability. The tibias were mechanically tested with the v-shape support under three-point bending using a Bose ElectroForce® 3200 until failure. The test revealed a significant result of flexural strength, work-to-fracture and strain to failure obtained from the load-displacement curves. The finding may be useful in the studies of quantitative assessments of the strength and toughness of small animal bones.